Catastrophic Health Expenditure and Poverty Impact Due to Mental Illness in India. (March 2023) - Yadav, Jeetendra; Allarakha, Shaziya; John, Denny; Menon, Geetha R.; Venkateswaran, Chitra; Singh, Ravinder
Majority of people in low- and middle-income countries with mental illness do not receive healthcare, leading to chronicity, suffering and increased costs of care. This study estimated the out-of-pocket expenditure (OOPE), catastrophic health expenditure (CHE), and poverty impact due to mental illness in India. Data was acquired from the 76th round data of the National Sample Survey (NSS) on the theme 'Persons with Disabilities in India Survey', July–December 2018. Data of 6, 679 persons who reported mental illness during the survey was included for analysis. OOPE, CHE, poverty impact and state differentials of healthcare expenditure on mental illness were analysed using standard methods. In total, 18.1% of the household's monthly consumption expenditure was spent on healthcare on mental illness. About 59.5% and 32.5% of the households were exposed to CHE based on 10% and 20% thresholds, respectively. About 20.7% of the households were forced to become poor from non-poor due to treatment care expenditure on mental illness. Our study suggests the critical need to accelerate on various measures for early diagnosis and management of mental health issues along with financial risk protection for reducing financial impact of healthcare expenditure on mental illness among households in India.